Currículo por projetos: inovação do ensinar e aprender na educação superior - Franco, Elize Keller (2008)
There have been plenty of claims for an innovative praxis in superior education. The conjunct of new references points to the production of knowledge from concrete social problematizations, integrated approaches to the knowledge, dialogical and formative relationship in the teaching-learning-evaluation process, among others. The present curricular order based on linear-technical disciplinary paradigm has been showing inadequate to articulate the range of changes required for innovation in superior education, putting the need to seek curricular models built under new bases, able to promote an integrated, complex , global and emancipatory of knowledge as a challenge. This research aims to make a reflection on the curriculum by projects, investigating the possibilities that it offers to an innovation in superior education. This is an exploratory descriptive analytic study of qualitative approach. The theoretical framework adopted in the process of finding the significant elements for a by project curricular organization is supported by authors such as Beherens (2006, 2004, 2000) Masetto (2006, 2004, 2003) Boutinet (2002) Zaballa (2002) Santomé (1998) Hernández ( 2000,1998) Leite (2001) Moesby (2004). The conceptual theoretical framework built from the theories of these authors about projects, curriculum and superior education led to the definition of analytical categories. The field research took place in UFPR Litoral, institution that has developed an alternative curricular organization and a pedagogic proposal based on projects. The data collected from interviews, observation and document analysis have led the empirical categories. The triangulation of analytical categories with the empirical categories brought indicators of the viability of organizing a curriculum by projects be an innovation in superior education as to be able to articulate a set of elements identified as relevant to a new praxis in this level of teaching